2021
DOI: 10.3390/vaccines9010061
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses Induced by mRNA Vaccination in Mice, Monkeys and Humans

Abstract: In this concise review, we summarize the concepts behind mRNA vaccination. We discuss the innate and adaptive immune response generated by mRNA vaccines in different animal models and in humans. We give examples of viral infections where mRNA vaccines have shown to induce potent responses and we discuss in more detail the recent SARS-CoV-2 mRNA vaccine trials in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 83 publications
2
114
0
Order By: Relevance
“…An important feature of the SARS-CoV-2 DNA vaccine is its ability to induce robust cellular as well as humoral immune responses (for reviews see [15][16][17][18][19][20][21]). In contrast to mRNA vaccines that induce robust antibody responses and low T cell responses, several clinical trials have shown that IM-as well as intradermal (ID)-delivered DNA vaccines [12,[56][57][58][59][60] Due to the differences in vaccine regimens, challenge virus stocks, animal facilities, methods to monitor immune responses, and virus load measurements used, it is challenging to make a comparison among the reported NHP studies.…”
Section: Post-challenge Immune Response Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An important feature of the SARS-CoV-2 DNA vaccine is its ability to induce robust cellular as well as humoral immune responses (for reviews see [15][16][17][18][19][20][21]). In contrast to mRNA vaccines that induce robust antibody responses and low T cell responses, several clinical trials have shown that IM-as well as intradermal (ID)-delivered DNA vaccines [12,[56][57][58][59][60] Due to the differences in vaccine regimens, challenge virus stocks, animal facilities, methods to monitor immune responses, and virus load measurements used, it is challenging to make a comparison among the reported NHP studies.…”
Section: Post-challenge Immune Response Analysismentioning
confidence: 99%
“…While different vaccine platforms are being used [reviewed in [1]], it is noteworthy that nucleic acid-based vaccines (mRNA and DNA) have been the faster to develop compared to approaches using recombinant viral vectors, protein, peptides or inactivated virus. The mRNA and DNA vaccine platforms are promising due to their simplicity, scalability, and in the case of viral vectors, the possibility of repeated applications due to the lack of immunity against the vector (for reviews see [15][16][17][18][19][20][21]). In contrast to mRNA vaccines that induce robust antibody responses but low T cell responses, several clinical trials have shown that intramuscular DNA vaccines induce both humoral and strong cellular immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in humans have been reviewed to reaffirm that free mRNA molecules released from the lipid nanoparticle are recognized by toll-like receptor 3 (TLR3), TLR7, TLR8, or retinoic acid-inducible gene (RIG-I), which activates type I interferon (IFN I) production and stimulates the Th1 response. On the one hand, ribosome translation is followed by proteasomal degradation, the peptides derived from which are presented by the major histocompatibility complex I (MHC-I), and, on the other hand, there is also MHC-II presentation resulting from APCs’ antigen uptake [ 111 ]. In lymph nodes, antigen presentation to T and B cells boosts the establishment of germinal centers, where antibody-producing cells are stimulated along with memory B cells [ 112 ].…”
Section: Vaccines In Clinical Developmentmentioning
confidence: 99%
“…Sequestration of virus in distal, 'sanctuary' tissues like the lower gastrointestinal tract, which is rich in ACE2 receptors clusters, has been reported clinically and in animal modeling studies that extend past a month of observation. There are few animal species that emulate the human condition and are consistent with the biological endpoints associated with COVID-19 and can be used as a disease model for evaluation [13][14][15] . The nonhuman primate, and specifically the rhesus macaque (Macaca mulatta) has emerged as a reasonable higher-order species from which advanced COVID-19 product evaluation studies can be performed.…”
Section: Introductionmentioning
confidence: 99%